Kangaroo: Multi-Hop protocol stack for Smart City sensor networks = Kangaroo: wieloskokowy stos protokołów dla sieci sensorowych Smart City - Maj, Jakub; Piotrowski, Krzysztof; Michta, Emil (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
This work presents the description of the Kangaroo Multi-Hop protocol stack used in Wireless Sensor Network solutions. The article presents the requirements for the stack, its structure and functions of the stack, as well as the types of information stored on the nodes and transferred between the nodes.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne